1130 ZEBRA HOOFBEATS: A RARE CASE OF STEMI IN GRANULOMATOUS NECROTIZING AORTITIS. (15th December 2022) - Facci, Gabriele; Alberti, Giorgia; Dotto, Alberto; Briani, Francesco; Benfari, Giovanni; Pighi, Michele; Ribichini, Flavio
Abstract: We present the unusual case of an AMI STEMI, complicated by ventricular fibrillation, in a 26 years old caucasic male patient, affected by necrotizing and granulomatous aortitis, in the context of a primary immunodeficiency. Initially the patient was referred to the Cardiology Unit for worsening dyspnea and fatigue. In his medical history he has primary immunodeficiency complicated by multiple opportunistic infections. We performed an echocardiography that revealed an aneurismatic ascending aorta (58 mm) with associated significant aortic valvular regurgitation. He was later referred to heart surgery OR where Bentall-De Bono operation was performed. Two years later he developed a lateral STEMI, complicated by ventricular fibrillation. The coronary angiography, performed in foreign country, showed total occlusion of the circumflex coronary artery with diffuse aneurismatic coronary disease, granulomatosis and ulcerative lesions. A percutaneous revascularization approach was tried, but ineffective. Actually the patient, during follow up, presents dilatative post-ischemic cardiopathy with moderate ejection fraction reduction, initial aortic bioprosthesis failure. We noted at follow up echocardiograms early dilatation of the native aortic arch (35 mm), suggesting a progressive disease. In conclusion, AMI's etiology includes many non atherosclerotic mechanisms that should be considered alongside common causes. This case shows a rare cause of STEMI in a very young male patient, and teaches us that aortitis is a progressive and complex pathology, often involving multiple arteriosus districts, that needs close follow-up and integrated management.